Emotion-driven impulsiveness but not decision-making ability and cognitive inflexibility predicts weight status in adults. (1st November 2019) - Coumans, Juul M.J.; Danner, Unna N.; Hadjigeorgiou, Charalambos; Hebestreit, Antje; Hunsberger, Monica; Intemann, Timm; Lauria, Fabio; Michels, Nathalie; Kurdiné, Eszter Molnár; Moreno, Luis A.; Reisch, Lucia A.; Thumann, Barbara F.; et al.
Abstract: In this study we aimed to determine whether decision-making ability, cognitive inflexibility and emotion-driven impulsiveness are associated with weight status as expressed by body mass index (BMI), percentage body fat, waist circumference and skinfold thickness in adults from eight different European countries taking part in the I.Family study. The Bechara Gambling Task was used to assess decision-making ability ( n  = 1717). The Berg Card Sorting Test was used to measure cognitive inflexibility ( n  = 1509). Lastly, the negative urgency subscale from the UPPS-P Impulsive Behavior Scale was used to measure emotion-driven impulsiveness ( n  = 4450). Hierarchical regression analyses showed that more emotion-driven impulsiveness was statistically significantly associated with a higher BMI, a higher percentage body fat, and a larger waist circumference in adults, controlling for age, sex, socioeconomic status, country and binge eating; but not with skinfold thickness. Cognitive inflexibility and decision-making ability were not statistically significantly associated with any of the weight status related variables. These results support that impulsivity in response to negative emotions, but not decision-making ability or cognitive inflexibility, is associated with the susceptibility to excessive weight (as indicated by a higher BMI, a higher percentage body fat, and a larger waist circumference). In people behaving impulsively when emotional, focusing on reducing negative affect or improving coping skills is of interest in interventions targeting obesity. Clinical trial registration: The I.Family study is registered in the ISRCTN registry (ISRCTN62310987) on February 23, 2018.